Перша бактеріологічна станція у харкові – архітектурна пам’ятка Слобожанщини - Євсюкова, О. О. (ХНУРЕ, 2020)
Each city has historical architectural monuments that form it as a "personality". Not only locals should know about them, but also foreign visitors. This work introduces the reader to the history of the creation of Institute of Microbiology and Immunology named after I. I. Mechnikov NAMS of Ukraine as an architectural monument of Kharkov.
Keywords: культурне розмаїття; українознавство; традиції; культура